Antioxidant activity-guided separation of coumarins and lignan from Melicope glabra (Rutaceae) - Kassim, Nur Kartinee; Rahmani, Mawardi; Ismail, Amin; Md.Sukari, Mohd. Aspollah; Ee, Gwendoline Cheng Lian; Md Nasir, Nadiah; Awang, Khalijah (Elsevier Science Limited, 2013)
The ethyl acetate and methanol bark extracts of Melicope glabra were evaluated for their antioxidant capacities by 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity and β-carotene bleaching/linoleic acid system. Both extracts exhibited strong inhibition against the DPPH radical (IC50 values of 24.81 and 13.01 μg ml(-1), respectively) and strong antioxidant activity in β-carotene bleaching assay. Both samples were found to have high phenolic content with values of 39 and 44 mg GAE/g as indicated by Follin-Ciocalteau's reagent. Antioxidant TLC assay-guided isolation on the methanol extract led to the isolation of a new pyranocoumarin, glabranin (1), umbelliferone (2), scopoletin (3) and sesamin (4), and their structures were determined by spectroscopy. Compounds (1-3) showed significant activities on DPPH free radical with the IC50 of 240.20, 810.02 and 413.19 μg ml(-1), respectively. However, in β-carotene bleaching assay, sesamin (4) showed higher inhibitory activity (1 mg ml(-1), 95%) than glabranin (1) (1 mg ml(-1), 74%), whilst umbelliferone (2) and scopoletin (3) were slightly pro-oxidant.